MEASURING EFFECT OF MODERM TECHNOLOGICAL PACKAGES ON THE PROFIT EFFICENCY OF WHEAT FARMERS IN IRAQ USING STOCHASTIC PROFIT FRONTIER FUNCTION. - & et al., Al-Hajami (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Using modern technology is one of the most important means that affect the productivity of wheat, the achievement of profits, the increase of agricultural production, and the progress towards self-sufficiency and food serenity. Therefore, the research aims to study the effects of the use of modern technological packages on the profits efficiency of wheat farms in Iraq for the season 2016-2017 in the provinces of  (Wasit, Babylon and Diwaniyah (, through estimation a stochastic profit frontier  function and inefficiency function. The results showed that the values of the parameters were significant and positive for the durum income and were significant and negative for the parameters of the production costs (mechanization, seeds, dab fertilizer, urea fertilizer and human working hours) .The parameters of the model of the inefficiency of profit were all negative and significant and this means the inverse effect of the use of modern technology has reduced the inefficiency of profit . Farmers recorded average efficiency in profit (77- 91)% depending on the type of technological package . This means that farmers can improve their efficiency by improving productivity and allocative efficiency. The research recommended the need to provide technology in quantities and numbers that cover the actual need to increase the efficiency of profit.